1901 Tex. Gen. Laws 53-54, Spec. Sess., An Act to Incorporate the City of Fort Worth and to Grant a New Charter to Said City, ch. 7, § 140. - (:unkn) unknown (My University, 1901)
The city council shall also have and possess the following express powers. . . To prohibit and restrain, or to regulate the firing of firecrackers, guns and pistols . . .
Keywords: DISCHARGE